Complex aestheticss treatment of six maxillary anterior teeth with smile design and deep bite correction - Nugraheni, Tunjung; Yulianasari, Yulianasari; Octarina, Lia Desire (Faculty of Dentistry, Universitas Gadjah Mada, 2023)
Dental trauma mostly damages the maxillary anterior teeth, affecting the individual’s esthetics, functionality, and psychological well-being. Restorative dentistry treatment is required to obtain a natural appearance based on the smile design approach. The aim of this report is to characterize the procedure of complicated cosmetic restoration of the six maxillary anterior teeth, which results in straighter and more beautiful natural-looking smiles. A 32-year-old male patient presented with multiple crown fractures in the anterior maxillary teeth, resulting in an unaesthetics smile. The patient also had a deep bite. A comprehensive aesthetics dental treatment was carried out. The dental treatment plan had to be carefully executed by considering several factors such as dental convexities and contours, re‑establishment of function, and esthetics. Smile design should always be approached as a multi-factor decision-making, which enables the doctor to treat patients using a personalized and interdisciplinary approach.